Implications of Regionalisation of the Direct Payment System – Research Results of French Institutes - Bryła, Paweł (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2009)
The paper aims at presenting selected implications of various paths of modification of the direct payment system on the basis of research results of leading agricultural policy institutes in France. The starting point for the presentation is an overview of French agriculture. Then, certain financial aspects of the current system of supporting French farmers from both European and national funds are examined. Furthermore, the issue of the direct payment system losing its legitimisation in its current shape (the historical model, partially decoupled) is raised. Against this background, the author quotes the results of three simulations of CAP reforms envisaging the replacement of the current system of support with various options of regionalisation of direct payments in France. The concluding remarks contain the principles of potential agricultural policy reforms which are essential from the French perspective.
Keywords: direct payments; regionalisation; France